IMPLIKASI YURIDIS NIKAH SIRI DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Nunung Nugroho (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2019)
Undang-Undang No. l Tahun 1974 In people's lives there is still a frequent way of marriage which is a violation of Law , especially article 2 paragraph 2, namely: "Each marriage is recorded according to the applicable laws and regulations". The definition of violation in the law, known as siri marriage. In this case the law must be understood as a set of rules governing, controlling society. Law in this sense is not part of the community system, but control of the community system. Law in this sense is not part of the community system, but control of the community system. According to Gustav Radbruch law must contain three basic values, namely: 1. Value of justice (philosophical aspect). The validity of the law is justified on the basis of human philosophical beliefs. 2. Value of certainty (juridical aspect). The law is enforced because it is determined by the state (gemeenschap), namely by the government and the people's representative council. 3. Value of benefits (sociological aspects). The validity of the law is due to social reality (society as a whole). In a sociological and philosophical view, siri marriage is relatively acceptable to the community, but judicially cannot be justified because it will have an impact on the low legal awareness of the community. Marriage recording does not determine the validity of a marriage, but only states that the marriage event actually happened, so it is merely administrative. Thus, the marriage is legitimate because it is carried out in accordance with religious law but has a weakness, namely the absence of a recording as referred to in article 2 paragraph 2 of  Undang-Undang No. l Tahun 1974 . In  reality the registration of marriages brought more good than bad in living in a society, so carrying out the registration of the marriage would be in line and not in conflict with religious norms